TREATMENT OF DISEASED MICEWITH CARCINOMA BY ACTIVATING THE IMMUNE CELLS BY SOFT LASER WITHOUT DRUGS - Khaleel, Aida Z (Al-Nahrain Journal of Science, 2010)
Regional immune response with mammary gland carcinoma has been studied statistically andhistologically. However, the prognostic value remains conflicting. This work was conducted on 30laboratory mice including healthy mice, and diseased mice with carcinoma not treated with laser(control group) and diseased mice with carcinoma treated with laser. The number of immune cellsof the lymph nodes was estimated by using a mesh lens which inserted into the eyepiece of themicroscope.The results showed significant increase in the number of immune cells of the lymph node of thediseased mice with carcinoma treated with laser in comparison with that of healthy mice anddiseased mice with carcinoma not treated with laser respectively.The histological examination of the prepared sections of the lymph nodes of the diseased micewith carcinoma treated with laser showed various changes in the structure of the immune cells suchas multiplication of the nucleus and cytoplasm cleavage due to laser stimulation.The gross observations proved that there was a decrease in tumor size of the diseased mice withcarcinoma after treatment with laser in comparison with not treated with laser.The aim of the study was to evaluate the effect of low level laser therapy (LLLT) on increasingthe response of immune system by stimulating the lymph node action in order to inhabit cancer cellactivity which leads to decrease the tumor size in diseased mice